An incident in mid-life of yucay Valley´s kuraka Francisco Chilche (1555) - Arana Bustamante, Luis (2009)
This study focused in an specific incident in Francisco Chilche’s life, registered by chronicler Inca Garcilaso de la Vega. In it, Chilche offended seriously to the Inka colonial nobilty at the Corpus Christi festivities in the main plaza of the city. Here it is offered an interpretation of the incident as an attempt of the kuraka to revert by the mid 1550´s his declination in prestige and social status in colonial city. I used as theoretical tools some of the methodological procedures associated to anthropological history.